Anticancer properties of bromelain: State-of-the-art and recent trends - Pezzani, Raffaele; Jiménez-Garcia, Manuel; Capó, Xavier; Sönmez Gürer, Eda; Sharopov, Farukh; Rachel, Tchokouaha Yamthe Lauve; Ntieche Woutouoba, David; Rescigno, Antonio; Peddio, Stefania; Zucca, Paolo; Tsouh Fokou, Patrick Valere; Martorell, Miquel; et al. (Frontiers in Oncology, 2023)
Bromelain is a key enzyme found in pineapple (Ananas comosus (L.) Merr.). It is a proteolytic substance with numerous health properties, ranging from anti-inflammatory, immunomodulatory, antioxidant, and anticancer, used ethnotraditionally for its potential therapeutic value in numerous countries. The aim of this updated and comprehensive review focuses on the potential anticancer benefits of bromelain, analyzing the cytotoxic, apoptotic, necrotic, autophagic, immunomodulating, and anti-inflammatory effects in cancer cells and animal models. Detailed information about Bromelain and its anticancer effects at the cellular, molecular and signaling levels were collected from online databases such as PubMed/MedLine, TRIP database, GeenMedical, Scopus, Web of Science and Google Scholar. The results of the analyzed studies showed that Bromelain possesses corroborated pharmacological activities, such as anticancer, anti-edema, anti-inflammatory, anti-microbial, anti-coagulant, anti-osteoarthritis, anti-trauma pain, anti-diarrhea, wound repair. Nonetheless, bromelain clinical studies are scarce and still more research is needed to validate the scientific value of this enzyme in human cancer diseases.